Barrier film and barrier packaging material
The barrier film, featuring a polyvinylidene chloride resin layer with a defined peak ratio and optional inorganic and adhesive layers, addresses the limitations of existing films by enhancing water vapor barrier properties and extending the shelf life of food packaging.
Patent Information
- Application Number
- JP2018248381
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2018-12-28
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2038-12-28
AI Technical Summary
Existing barrier films, particularly those using polyvinylidene chloride resin, face challenges in extending the expiration date of food packaging and improving water vapor and oxygen barrier properties.
A barrier film comprising a polyvinylidene chloride resin layer with a specific infrared absorption spectrum peak ratio, which includes a substrate film layer and an optional inorganic layer, and may feature a polyester adhesive layer for enhanced adhesion.
The proposed barrier film achieves excellent water vapor barrier properties without the need for a deposited film or an excessively thick polyvinylidene chloride layer, thereby extending the shelf life of packaged foods.
Smart Images

Figure 0007663311000002 
Figure 0007663311000003 
Figure 0007663311000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a barrier film and a barrier packaging material. [Background technology]
[0002] A known barrier film has an inorganic layer and a polyvinylidene chloride resin layer provided on the surface of a base film layer. An example of a technique relating to such a barrier film is described in Patent Document 1 (JP-A-08-39718).
[0003] Patent Document 1 describes a composite vapor-deposited film characterized in that a vapor-deposited film (B) of an inorganic material is formed on at least one surface of a polymer film substrate (A), and further, a coating film (C) of polyvinylidene chloride is laminated on the vapor-deposited film (B). Patent Document 1 describes that such a composite vapor-deposited film has excellent gas barrier properties and resistance to flexural fatigue. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 08-39718 Summary of the Invention [Problem to be solved by the invention]
[0005] As mentioned above, various technologies using vinylidene chloride as a barrier film have been proposed, but for food packaging applications, there is a demand to extend the shelf life of the contents, and therefore there is a need for further improvements in the barrier properties against water vapor and oxygen. The present invention has been made in view of the above circumstances, and has an object to provide a barrier film having excellent water vapor barrier properties in particular. [Means for solving the problem]
[0006] According to the present invention, there is provided the following barrier film.
[0007] [1] A barrier film comprising at least a polyvinylidene chloride resin layer containing a polyvinylidene chloride resin as a main component, In the infrared absorption spectrum of the polyvinylidene chloride resin layer, -1 Absorption peak height A(1070) at wavenumbers near 1046 cm -1 A barrier film having a peak ratio (A(1046) / A(1070)) of absorption peak heights A(1046) at wave numbers in the vicinity of 2.10 or more. [2] [1] The barrier film according to the present invention, A barrier film having a base film layer on at least one side of the polyvinylidene chloride resin layer. [3] [2] The barrier film according to the present invention, A barrier film having an inorganic layer between the polyvinylidene chloride resin layer and the base film layer. [4] [3] The barrier film according to the present invention, The barrier film, wherein the inorganic layer contains one or more inorganic materials selected from the group consisting of silicon oxide, silicon oxynitride, silicon nitride, aluminum oxide, and aluminum. [5] [1] to [4], wherein the barrier film is A barrier film having a polyester-based adhesive layer between the base film layer and the polyvinylidene chloride-based resin layer. [6] [1] to [5], wherein the barrier film is The polyvinylidene chloride resin layer comprises one or more adhesive components selected from the group consisting of a silane coupling agent, a urethane resin, a urea resin, a melamine resin, an epoxy resin, and an alkyd resin. [7] A barrier packaging material comprising the barrier film according to any one of [1] to [6]. Effect of the Invention
[0008] According to the present invention, a polyvinylidene chloride barrier film having excellent water vapor barrier properties can be provided. Furthermore, according to the present invention, a vapor deposition film is not necessarily required, and excellent water vapor barrier properties can be obtained without making the polyvinylidene chloride layer extremely thick (for example, 10 μm or more). [Brief description of the drawings]
[0009] [Figure 1] 1 is a cross-sectional view showing a schematic example of the structure of a laminated film of the present embodiment. [Diagram 2] FIG. 2 is a diagram showing IR peaks of the laminated film of the present embodiment. [Diagram 3] FIG. 1 is a cross-sectional view showing a schematic example of a structure of a barrier film according to an embodiment of the present invention. [Figure 4] FIG. 2 is a diagram showing the water vapor transmission rate (WVTR) of the laminated film structure of the present embodiment. [Diagram 5] FIG. 2 is a diagram showing the relative crystallinity obtained from the IR peak intensity ratio of the laminated film of the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In all drawings, similar components are given similar reference symbols, and descriptions will be omitted as appropriate. The drawings are schematic views and do not correspond to the actual dimensional ratios. Unless otherwise specified, "~" between numbers in the text indicates from above to below.
[0011] [Barrier film] FIG. 1 is a cross-sectional view showing a schematic example of the structure of a barrier film 100 according to an embodiment of the present invention. The barrier film 100 according to this embodiment includes at least a first barrier resin layer (A1) containing a polyvinylidene chloride resin as a main component and a resin film layer. -1 Absorption peak height A(1070) at wavenumbers near 1046 cm -1 The peak ratio (A(1046) / A(1070)) (hereinafter, sometimes referred to simply as "peak ratio") of the absorption peak heights A(1046) at wave numbers in the vicinity of is 2.10 or more. When the peak ratio is 2.10 or more, the water vapor barrier property of the barrier film 100 can be made good. The peak ratio is preferably 2.20 or more, more preferably 2.30 or more. The upper limit is not particularly limited, but is, for example, 8.0 or less, or 6.0 or less.
[0012] Here, the above peak ratio of the first barrier resin layer (A1) is an index of the crystallinity of the polyvinylidene chloride resin. -1 The peak value (A(1070)) in the vicinity is a peak value indicating an amorphous region, and the larger the amorphous region, the larger the peak value. -1 The peak value of the nearby wave number (A(1046)) is the peak value that indicates the crystalline region, and the larger the crystalline region, the larger the peak value. Therefore, the larger the peak ratio, the higher the crystallinity, and the smaller the peak ratio, the lower the crystallinity.
[0013] As a specific method for measuring the peak ratio, a measurement sample of 1 cm × 3 cm is cut out from the barrier film 100, and the infrared absorption spectrum of the surface (first barrier resin layer (A1)) is obtained by infrared total reflection measurement (ATR method), and the peak ratio (A(1046) / A(1070)) is calculated. The infrared spectrum was measured (attenuated total reflection (ATR) method) using a JASCO FT-IR350 instrument, equipped with a KRS-5 (Thallium Bromide-Iodide) crystal, at an incidence angle of 45 degrees, at room temperature, and with a resolution of 4 cm. -1 The test is performed with 150 cumulative measurements. In the infrared spectrum chart obtained by measuring under the above conditions, -1 Nearby absorbance minima A(1085) and 1060cm -1 Connect the nearest minimum absorbance value A (1060) with a straight line (N) and -1 A line drawn perpendicularly from the maximum absorbance value in the vicinity to line (N) is called line (O), and the intersection point between line (O) and line (N) and the 1070 cm -1 The distance from the maximum absorbance value in the vicinity is defined as the absorption peak height A (1070). Also, 1010cm -1 Nearby absorbance minima A(1010) and 1060cm -1 Connect the nearest minimum absorbance value A (1060) with a straight line (M) and -1 A line drawn perpendicularly from the maximum absorbance value in the vicinity to the line (M) is called a line (P), and the intersection point between the line (P) and the line (M) and the 1046 cm -1 The distance from the maximum absorbance value in the vicinity is defined as the absorption peak height A (1046).
[0014] For reference, Figure 2 provides additional information on how to read an infrared spectrum chart.
[0015] In this embodiment, factors for controlling the crystallinity of the polyvinylidene chloride resin include appropriately selecting the type of polyvinylidene chloride resin, aging the first barrier resin layer (A1) containing a polyvinylidene chloride resin as a main component, and the heating conditions for the aging.
[0016] The barrier resin layer (A1) is preferably a barrier resin layer formed from a polyvinylidene chloride resin solution obtained by dissolving a polyvinylidene chloride resin in an organic solvent. The organic solvent for dissolving the polyvinylidene chloride resin is not particularly limited since it is appropriately selected according to the type of polyvinylidene chloride resin used, but examples thereof include ketones such as acetone, methyl ethyl ketone, cyclohexanone, etc.; ethers such as dioxane, diethyl ether, tetrahydrofuran, etc.; aromatic hydrocarbons such as benzene, toluene, xylene, etc.; esters such as ethyl acetate, butyl acetate, etc.; amides such as dimethylformamide, etc.; mixed solvents thereof, etc. In particular, it is preferable to contain a mixture of at least two selected from aromatic solvents, ketone-based solvents, and ether-based solvents, and among these, a mixed solvent of tetrahydrofuran and toluene, a mixed solvent of methyl ethyl ketone and toluene, or a mixed solvent of tetrahydrofuran, toluene, and methyl ethyl ketone is preferred. The polyvinylidene chloride resin solution is preferably used after being completely dissolved in a solvent and then left to stand for 24 to 168 hours, preferably 72 to 120 hours, after preparation of the solution. It is preferable that the solution becomes opaque after storage. The reason for this is unclear, but it is assumed that by storing and curing the solution for a certain period of time, the crystallization of the precipitated resin progresses, contributing to the barrier properties.
[0017] The present inventors have newly discovered that the barrier property of a barrier film comprising at least a polyvinylidene chloride resin layer can be improved by adjusting the peak ratio of the first barrier resin layer (A1) to the above lower limit or more. That is, according to this embodiment, by making the peak ratio of the first barrier resin layer (A1) equal to or greater than the above lower limit, it is possible to realize a polyvinylidene chloride barrier film 100 with excellent barrier properties. The reason for this is unclear, but it is presumed that in a liquid that has become opaque due to the composition of the solvent and storage and curing, the precipitated resin forms plate-like lamellae, and when the peak ratio is above the lower limit above, that is, when the crystallinity is above a certain value, the area with a denser crystal structure becomes larger and when a coating is formed, the precipitated resin tends to become plate-like crystals, which are aligned parallel to the substrate surface and create a so-called labyrinth effect in the gas permeation mechanism. It is believed that gases such as oxygen and water vapor become less likely to permeate, and the barrier properties can be improved at the same time.
[0018] (Polyvinylidene chloride resin layer) From the viewpoint of obtaining excellent barrier performance, the barrier film 100 according to this embodiment includes at least a first barrier resin layer (A1) containing a polyvinylidene chloride resin as a main component. The first barrier resin layer (A1) is a layer containing a polyvinylidene chloride resin as a main component. The first barrier resin layer (A1) may be composed of one polyvinylidene chloride resin layer or two or more polyvinylidene chloride resin layers, which may be the same type of polyvinylidene chloride resin layer or different types of polyvinylidene chloride resin layers.
[0019] Here, containing a polyvinylidene chloride resin as a main component means that the first barrier resin layer (A1) contains 50% by mass or more of a polyvinylidene chloride resin. The first barrier resin layer (A1) contains preferably 60% by mass or more of a polyvinylidene chloride resin, more preferably 70% by mass or more, even more preferably 80% by mass or more, still more preferably 90% by mass or more, and particularly preferably 100% by mass. When the content of the polyvinylidene chloride resin in the first barrier resin layer (A1) is within the above range, the balance of blocking resistance and barrier properties becomes even more excellent.
[0020] The polyvinylidene chloride resin of the present embodiment is not particularly limited as long as it mainly contains vinylidene chloride monomer as a constituent unit, and may be polyvinylidene chloride (PVDC) containing 100% by mass of vinylidene chloride, or may be a copolymer of vinylidene chloride and a monomer copolymerizable with vinylidene chloride.
[0021] An example of the copolymer is one having a vinylidene chloride content of 60% by mass or more and less than 100% by mass, and a content of a monomer copolymerizable with vinylidene chloride of more than 0% by mass and not more than 40% by mass. Examples of monomers copolymerizable with vinylidene chloride include (meth)acrylic acid esters such as alkyl esters or cycloalkyl esters of (meth)acrylic acid having 1 to 18 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, glycidyl (meth)acrylate, cyclohexyl (meth)acrylate, n-octyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, and stearyl (meth)acrylate, and alkoxyalkyl esters of (meth)acrylic acid having 2 to 18 carbon atoms, such as methoxybutyl (meth)acrylate, methoxyethyl (meth)acrylate, and ethoxybutyl (meth)acrylate; (meth)acrylic acid, crotonic acid, itaconic acid, itaconic anhydride, maleic acid, maleic anhydride, fumaric acid, cycloalkyl esters of (meth)acrylic acid having 2 to 18 carbon atoms, such as methoxybutyl (meth)acrylate, methoxyethyl (meth)acrylate, and ethoxybutyl (meth)acrylate, and cycloalkyl esters of (meth)acrylic acid having 2 to 18 carbon atoms, such as methoxybutyl (meth)acrylate, methoxyethyl (meth)acrylate, and ethoxybutyl (meth)acrylate. Examples of the monomer may include one or more selected from ethylenic α,β-unsaturated carboxylic acids having a carboxyl group, such as traconic acid, and salts thereof; unsaturated amide compounds, such as (meth)acrylamide and diacetone acrylamide; nitrile group-containing monomers, such as acrylonitrile and methacrylonitrile; acrylic acid or hydroxyalkyl esters of (meth)acrylic acid having 2 to 8 carbon atoms, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate; hydroxyl group-containing monomers, such as polyoxyethylene monoacrylate, polyoxyethylene monomethacrylate, N-methylol (meth)acrylamide, and allyl alcohol; and other polymerizable unsaturated monomers, such as styrene, α-methylstyrene, vinyl chloride, butadiene, vinyl toluene, vinyl acetate, itaconic acid alkyl esters, ethylene, propylene, and isobutylene.
[0022] The first barrier resin layer (A1) can be formed, for example, from a polyvinylidene chloride resin solution prepared by dissolving a polyvinylidene chloride resin in an organic solvent.
[0023] The polyvinylidene chloride resin used in the first barrier resin layer (A1) can be produced by a conventionally known method, but various commercially available products can also be used. As a commercially available product, the Saran Resin series manufactured by Asahi Kasei Corporation can be preferably used.
[0024] The organic solvent for dissolving the polyvinylidene chloride resin is not particularly limited since it is appropriately selected according to the type of polyvinylidene chloride resin used, but examples thereof include ketones such as acetone, methyl ethyl ketone, cyclohexanone, etc.; ethers such as dioxane, diethyl ether, tetrahydrofuran, etc.; aromatic hydrocarbons such as benzene, toluene, xylene, etc.; esters such as ethyl acetate, butyl acetate, etc.; amides such as dimethylformamide, etc.; mixed solvents thereof; etc. These organic solvents may be used alone or in combination of two or more. Among these, a mixed solvent of tetrahydrofuran and toluene, a mixed solvent of methyl ethyl ketone and toluene, and a mixed solvent of tetrahydrofuran, toluene and methyl ethyl ketone are preferable.
[0025] The first barrier resin layer (A1) may further contain an adhesive component from the viewpoint of improving adhesion to the base film layer 103 and the inorganic layer 105. In particular, when a layer formed of silicon oxide is used as the inorganic layer 105, it is preferable that the first barrier resin layer (A1) further contains an adhesive component from the viewpoint of improving adhesion between the first barrier resin layer (A1) and the inorganic layer 105. As the adhesive component, it is preferable to use one or more types selected from the group consisting of silane coupling agents; and adhesive resins such as urethane-based resins, urea-based resins, melamine-based resins, epoxy-based resins, and alkyd-based resins.
[0026] The silane coupling agent is not particularly limited, and examples thereof include halogen-containing silane coupling agents such as 2-chloroethyltrimethoxysilane, 2-chloroethyltriethoxysilane, 3-chloropropyltrimethoxysilane, and 3-chloropropyltriethoxysilane; epoxy group-containing silane coupling agents such as 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 3-(3,4-epoxycyclohexyl)propyltrimethoxysilane, 2-glycidyloxyethyltrimethoxysilane, 2-glycidyloxyethyltriethoxysilane, 3-glycidyloxypropyltrimethoxysilane, and 3-glycidyloxypropyltriethoxysilane; 2-aminoethyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 2-[N-(2-aminoethyl)amino]ethyltrimethoxysilane, 3- [N-(2-aminoethyl)amino]propyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, 3-[N-(2-aminoethyl)amino]propylmethyldimethoxysilane and other amino group-containing silane coupling agents; 2-mercaptoethyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane and other mercapto group-containing silane coupling agents; vinyltrimethoxysilane, vinyltriethoxysilane and other vinyl group-containing silane coupling agents; 2-methacryloyloxyethyltrimethoxysilane, 2-methacryloyloxyethyltriethoxysilane, 2-acryloyloxyethyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropyltriethoxysilane, 3-acryloyloxypropyltrimethoxysilane and other (meth)acryloyl group-containing silane coupling agents. These silane coupling agents may be used alone or in combination of two or more.
[0027] For example, the first barrier resin layer (A1) containing an adhesive component can be formed by using a polyvinylidene chloride resin solution obtained by dissolving an adhesive component in an organic solvent together with a polyvinylidene chloride resin.
[0028] The barrier film 100 has excellent oxygen barrier properties and can be suitably used as a packaging film or a sealing film. Specifically, the barrier film 100 preferably has an oxygen permeability of 2.0 ml / m2 measured in accordance with JIS K7126-2:2006 at a temperature of 20° C. and a humidity of 90% RH. 2 ·day·MPa or less, and more preferably 1.5ml / m 2 ·day·MPa or less, and more preferably 1.0 ml / m 2 ·day·MPa or less, and even more preferably 0.5ml / m 2 ·day·MPa or less. Such oxygen permeability can be appropriately adjusted by controlling the crystallinity of the first barrier resin layer (A1), in addition to adjusting the thickness of the first barrier resin layer (A1) and adding or adjusting the thickness of an inorganic layer.
[0029] The barrier film 100 has excellent water vapor barrier properties and can be suitably used as a packaging film or a sealing film. Specifically, the barrier film 100 has a water vapor permeability of preferably 10 g / m2 measured under conditions of a temperature of 40° C. and a humidity of 90% RH. 2 ·day or less, preferably 5g / m 2 day or less, particularly preferably 3 g / m 2 ·day or less. Such water vapor permeability can be appropriately adjusted by controlling the crystallization degree of the first barrier resin layer (A1), in addition to adjusting the thickness of the first barrier resin layer (A1), adding an inorganic layer or adjusting its thickness, etc.
[0030] Although the total thickness of the barrier film 100 according to this embodiment is not particularly limited, the first barrier resin layer (A1) has excellent barrier properties, so that the film can be thinned. Specifically, a barrier film having a total thickness of 15 μm or less is also possible.
[0031] From the viewpoint of a balance between barrier properties, transparency, handleability, etc., when the barrier film 100 does not include the base film layer 103, the thickness of the first barrier resin layer (A1) is preferably from 0.2 μm to 50 μm, more preferably from 0.5 μm to 30 μm, and even more preferably from 1 μm to 20 μm.
[0032] From the viewpoint of a balance between barrier properties, transparency, handleability, etc., when the barrier film 100 includes the base film layer 103, the thickness of the first barrier resin layer (A1) is preferably from 0.05 μm to 20 μm, more preferably from 0.1 μm to 10 μm, even more preferably from 0.3 μm to 5 μm, still more preferably from 0.5 μm to 3 μm, and particularly preferably from 0.5 μm to 1 μm.
[0033] Examples of methods for forming the first barrier resin layer (A1) include a method of laminating a polyvinylidene chloride resin film formed from a polyvinylidene chloride resin solution onto the base film layer 103, the inorganic layer 105, or another base material to form the first barrier resin layer (A1), and a method of applying a polyvinylidene chloride resin solution onto the base film layer 103, the inorganic layer 105, or another base material and drying to form the first barrier resin layer (A1). Among these, from the viewpoints of barrier properties, adhesion, productivity, etc., the method of applying a polyvinylidene chloride resin solution onto the base film layer 103, the inorganic layer 105, or another base material and drying to form the first barrier resin layer (A1) is preferred.
[0034] It is preferable that a second barrier film layer A2 is further laminated on the surface of the first barrier film A1 opposite to the inorganic layer. Resin film layer / inorganic layer / first barrier resin layer (A1) / barrier resin layer (A2) The layer structure is preferable. The second barrier film A2 is preferably a layer formed from a latex containing fine particles of a polyvinylidene chloride resin. Examples of the method for forming the second barrier film A2 include a method for laminating a polyvinylidene chloride resin film formed from latex containing fine particles of polyvinylidene chloride resin onto the base film layer 103, the inorganic layer 105, or another base material to form the polyvinylidene chloride resin layer 101, and a method for applying latex containing fine particles of polyvinylidene chloride resin onto the base film layer 103, the inorganic layer 105, or another base material and drying it to form the polyvinylidene chloride resin layer 101. Among these, from the viewpoints of barrier properties, adhesion, and productivity, the method for applying latex containing fine particles of polyvinylidene chloride resin onto the base film layer 103, the inorganic layer 105, or another base material and drying it to form the polyvinylidene chloride resin layer 101 is preferred. Furthermore, by repeating or combining the above-mentioned method for forming a polyvinylidene chloride-based resin layer using the polyvinylidene chloride-based resin solution or latex containing fine particles of polyvinylidene chloride-based resin two or more times, it is possible to form a polyvinylidene chloride-based resin layer 101 composed of two or more polyvinylidene chloride-based resin layers.
[0035] (Base film layer) As shown in FIG. 1, in the barrier film 100 according to this embodiment, a base film layer 103 may be further laminated on at least one surface of the first barrier resin layer (A1).
[0036] The base film layer 103 of this embodiment preferably contains a thermoplastic resin, and more preferably is composed of a sheet-like or film-like base material formed of a thermoplastic resin. As the thermoplastic resin, a known thermoplastic resin can be used. For example, one or more selected from polyolefins such as polyethylene, polypropylene, poly(4-methyl-1-pentene), and poly(1-butene); polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyamides such as nylon-6, nylon-66, and polymetaxylene adipamide; polyvinyl chloride; polyimide; ethylene-vinyl acetate copolymer; polyacrylonitrile; polycarbonate; polystyrene; ionomer; and the like can be used. Among these, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polyamide are preferred because of their excellent stretchability and transparency.
[0037] The film-like substrate made of a thermoplastic resin may be either a non-stretched film or a stretched film. In addition, one or both sides of the base film layer 103 may be subjected to a surface activation treatment such as corona treatment, flame treatment, plasma treatment, primer coating treatment, etc., in order to improve adhesion to the inorganic layer 105 or the first barrier resin layer (A1). The thickness of the base film layer 103 is usually 1 μm or more and 200 μm or less, and preferably 5 μm or more and 150 μm or less.
[0038] (Inorganic layer) 3, in the barrier film 100, an inorganic layer 105 may be further laminated between the first barrier resin layer (A1) and the base film layer 103. This can further improve the barrier properties such as oxygen barrier property and water vapor barrier property while maintaining good blocking resistance. Examples of inorganic materials constituting the inorganic layer 105 of this embodiment include metals and metal oxides that can form thin films having barrier properties. Examples of inorganic materials constituting the inorganic layer 105 include one or more selected from the group consisting of simple substances or oxides of elements from Group 2A of the periodic table, such as beryllium, magnesium, calcium, strontium, barium, etc.; transition elements from the periodic table, such as titanium, zirconium, ruthenium, hafnium, tantalum, etc.; elements from Group 2B of the periodic table, such as zinc, etc.; elements from Group 3A of the periodic table, such as aluminum, gallium, indium, thallium, etc.; elements from Group 4A of the periodic table, such as silicon, germanium, tin, etc.; and elements from Group 6A of the periodic table, such as selenium, tellurium, etc. In this embodiment, the names of elements in the periodic table are shown in the old CAS system.
[0039] Furthermore, among the above inorganic substances, one or more inorganic substances selected from the group consisting of silicon oxide, silicon oxynitride, silicon nitride, aluminum oxide, and aluminum are preferred because they have an excellent balance of barrier properties, costs, and the like. The silicon oxide may contain silicon monoxide and silicon suboxide in addition to silicon dioxide.
[0040] The inorganic layer 105 is formed from the above-mentioned inorganic material. The inorganic layer 105 may be composed of a single inorganic layer, or may be composed of multiple inorganic layers. When the inorganic layer 105 is composed of multiple inorganic layers, the inorganic layers may be the same type, or different types.
[0041] From the viewpoint of a balance between barrier properties, adhesion, ease of handling, and the like, the thickness of the inorganic layer 105 is preferably 1 nm or more and 500 nm or less, more preferably 2 nm or more and 300 nm or less, and further preferably 5 nm or more and 150 nm or less. In this embodiment, the thickness of the inorganic layer 105 can be determined from an image observed with a transmission electron microscope or a scanning electron microscope.
[0042] The method for forming the inorganic layer 105 is not particularly limited, and for example, the inorganic layer 105 can be formed on one or both sides of the base film layer 103 by a vacuum process such as vacuum deposition, sputtering, or plasma chemical vapor deposition (CVD), or a sol-gel process.
[0043] (Polyester adhesive layer) Furthermore, in order to improve the interlayer peel strength, a polyester adhesive layer can be provided between the base film layer 103 and the first barrier resin layer (A1). In particular, when the first barrier resin layer (A1) made of latex containing fine particles of polyvinylidene chloride resin is formed on the base film layer 103 or on the inorganic layer 105 provided on the surface of the base film layer 103, it is preferable to form the first barrier resin layer (A1) via a polyester adhesive layer from the viewpoint of improving and stabilizing the interlayer peel strength.
[0044] The polyester adhesive layer is preferably formed from, for example, a polyester polyol and a curing agent such as a polyisocyanate.
[0045] The polyester polyol is a polyester obtained by reacting a polyvalent carboxylic acid with a polyol. The polyol used as a raw material is a compound having at least two hydroxyl groups in the molecule, and examples of the polyol include low molecular weight polyols and high molecular weight polyols.
[0046] Examples of low molecular weight polyols include ethylene glycol, propanediol, 1,4-butylene glycol, 1,3-butylene glycol, 1,2-butylene glycol, 1,6-hexanediol, neopentyl glycol, alkane (C7 to C22) diols, diethylene glycol, triethylene glycol, dipropylene glycol, cyclohexanedimethanol, alkane-1,2-diols (C17 to C20), bisphenol A, hydrogenated bisphenol A, 1,4-dihydroxy-2-butene, 2,6-dimethyl-1-octene-3,8-diol, bishydroxyethoxybenzene, and cyclohexanedimethanol. Examples of such low molecular weight diols include styrene glycol and bishydroxyethylene terephthalate; low molecular weight triols such as glycerin, 2-methyl-2-hydroxymethyl-1,3-propanediol, 2,4-dihydroxy-3-hydroxymethylpentane, 1,2,6-hexanetriol, 1,1,1-tris(hydroxymethyl)propane, 2,2-bis(hydroxymethyl)-3-butanol, and other aliphatic triols (C8 to C24); and low molecular weight polyols having four or more hydroxyl groups such as tetramethylolmethane, D-sorbitol, xylitol, D-mannitol, and D-mannite.
[0047] Examples of high molecular weight polyols include polyether polyols, polyester polyols, polycarbonate polyols, acrylic polyols, epoxy polyols, natural oil polyols, silicon polyols, fluorine polyols, and polyolefin polyols.
[0048] In addition, examples of polyester polyols include one or more of the low molecular weight polyols described above, or one or more of the high molecular weight polyols, and, for example, oxalic acid, malonic acid, succinic acid, methylsuccinic acid, glutaric acid, adipic acid, 1,1-dimethyl-1,3-dicarboxypropane, 3-methyl-3-ethylglutaric acid, azelaic acid, sebacic acid, other aliphatic dicarboxylic acids (C11 to C13), hydrogenated dimer acids, maleic acid, fumaric acid, itaconic acid, orthophthalic acid, isophthalic acid, tetrahydrofuran ... Examples of the polyester polyols include carboxylic acids such as benzoic acid, toluene dicarboxylic acid, dimer acid, and HET acid, and acid anhydrides derived from these carboxylic acids, such as oxalic anhydride, succinic anhydride, maleic anhydride, phthalic anhydride, 2-alkyl (C12 to C18) succinic anhydride, tetrahydrophthalic anhydride, and trimellitic anhydride, and acid halides derived from these carboxylic acids, such as oxalic acid dichloride, adipic acid dichloride, and sebacic acid dichloride.
[0049] The polyisocyanate, which is a curing agent for forming the polyester-based adhesive layer according to this embodiment, is a compound having at least two isocyanate groups in the molecule, and examples thereof include aromatic polyisocyanates, araliphatic polyisocyanates, alicyclic polyisocyanates, and aliphatic polyisocyanates.
[0050] Examples of aromatic polyisocyanates include aromatic diisocyanates such as m-phenylene diisocyanate, p-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, 4,4'-diphenylmethane diisocyanate (MDI), 2,4- or 2,6-tolylene diisocyanate (TDI) or a mixture thereof, 4,4'-toluidine diisocyanate, and 4,4'-diphenylether diisocyanate; aromatic triisocyanates such as triphenylmethane-4,4',4''-triisocyanate, 1,3,5-triisocyanate benzene, and 2,4,6-triisocyanate toluene; and aromatic tetraisocyanates such as 4,4'-diphenylmethane-2,2',5,5'-tetraisocyanate.
[0051] Examples of the aromatic aliphatic polyisocyanate include aromatic aliphatic diisocyanates such as 1,3- or 1,4-xylylene diisocyanate (XDI) or a mixture thereof, ω,ω'-diisocyanato-1,4-diethylbenzene, 1,3- or 1,4-bis(1-isocyanato-1-methylethyl)benzene (TMXDI) or a mixture thereof; and aromatic aliphatic triisocyanates such as 1,3,5-triisocyanatomethylbenzene.
[0052] Examples of alicyclic polyisocyanates include alicyclic diisocyanates such as 1,3-cyclopentane diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate (IPDI), 4,4'-methylenebis(cyclohexyl isocyanate) (H12MDI), methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 1,3- or 1,4-bis(isocyanatomethyl)cyclohexane (H6XDI) or mixtures thereof; 1,3,5-triisocyanatocyclohexane, 1,3,5-trimethylisocyanatocyclohexane, 2-(3-isocyanatopropyl)-2,5-di(isocyanatomethyl)-bicyclo(2.2.1)heptane, 2-(3 -isocyanatopropyl)-2,6-di(isocyanatomethyl)-bicyclo(2.2.1)heptane, 3-(3-isocyanatopropyl)-2,5-di(isocyanatomethyl)-bicyclo(2.2.1)heptane, 5-(2-isocyanatoethyl)-2-isocyanatomethyl-3-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane, 6-(2-isocyanatoethyl)-2-isocyanato alicyclic triisocyanates such as 3-(3-isocyanatepropyl)-bicyclo(2.2.1)heptane, 5-(2-isocyanateethyl)-2-isocyanatemethyl-2-(3-isocyanatepropyl)-bicyclo(2.2.1)heptane, and 6-(2-isocyanateethyl)-2-isocyanatemethyl-2-(3-isocyanatepropyl)-bicyclo(2.2.1)heptane.
[0053] Examples of aliphatic polyisocyanates include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (HDI), pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, 2,4,4- or 2,2,4-trimethylhexamethylene diisocyanate, 2,6-di ... aliphatic diisocyanates such as isocyanate methyl caproate; and aliphatic triisocyanates such as lysine ester triisocyanate, 1,4,8-triisocyanate octane, 1,6,11-triisocyanate undecane, 1,8-diisocyanate-4-isocyanate methyl octane, 1,3,6-triisocyanate hexane, and 2,5,7-trimethyl-1,8-diisocyanate-5-isocyanate methyl octane.
[0054] These polyisocyanates may be used alone or in combination of two or more thereof. Preferred are aromatic, araliphatic, alicyclic and aliphatic diisocyanates.
[0055] (Heat-sealing layer) The barrier film 100 of this embodiment may have a heat-sealable layer on at least one surface thereof in order to impart heat-sealability. The heat-sealing layer may be any known heat-sealing layer, including, for example, a layer formed of a resin composition containing one or more polyolefins selected from homopolymers or copolymers of α-olefins such as ethylene, propylene, butene-1, hexene-1, 4-methyl-pentene-1, octene-1, etc., high-pressure low-density polyethylene, linear low-density polyethylene (so-called LLDPE), high-density polyethylene, polypropylene, polypropylene random copolymer, low-crystalline or non-crystalline ethylene-propylene random copolymer, ethylene-butene-1 random copolymer, propylene-butene-1 random copolymer, etc., a layer formed of a resin composition containing ethylene-vinyl acetate copolymer (EVA), and a layer formed of a resin composition containing EVA and polyolefin.
[0056] (Other layers) The barrier film 100 of this embodiment may further be provided with various coating layers or laminate layers, such as a lubricating layer or an antistatic layer.
[0057] (Application) The barrier film 100 of the present embodiment can be suitably used, for example, as a packaging film for packaging foods, medicines, daily necessities, etc., which require barrier performance; a film for vacuum insulation panels; a sealing film for sealing electroluminescence elements, solar cells, etc.; etc. The barrier film 100 of this embodiment can also be suitably used as a barrier film constituting a barrier packaging body. The barrier packaging body according to this embodiment is, for example, a barrier packaging bag itself made of the barrier film 100 of this embodiment used for the purpose of filling it with contents, or the bag filled with contents. The barrier packaging bag according to this embodiment may use the barrier film 100 in a part thereof, or the barrier film 100 may be used for the entire barrier packaging bag, depending on the application.
[0058] [Method of manufacturing barrier film] The method for producing the barrier film 100 according to this embodiment includes, for example, the following steps. (1) A step of dissolving a polyvinylidene chloride resin in an organic solvent and storing the polyvinylidene chloride resin solution at about room temperature for 24 to 168 hours, preferably 72 to 120 hours, to promote crystallization. As the organic solvent, a mixture of a good solvent (such as THF) and a poor solvent (such as toluene) can be used. Also, after completely dissolving in the good solvent, the poor solvent can be added. The degree of crystallization can be confirmed by pouring the solution into a transparent container such as a glass bottle and observing the degree of turbidity. (2) A step of forming a first barrier resin layer (A1) by applying a polyvinylidene chloride-based resin solution obtained by dissolving a polyvinylidene chloride-based resin in an organic solvent onto the base film layer 103, the inorganic layer 105, or other base material, and drying the applied solution;
[0059] In the above step (2), the method for applying the polyvinylidene chloride resin solution onto the base film layer 103, the inorganic layer 105, or other base material, and the method for applying the latex containing fine particles of polyvinylidene chloride resin onto the base film layer 103, the inorganic layer 105, or other base material are not particularly limited, and a conventional method can be used. For example, a coating method using a known coater such as an air knife coater, a kiss roll coater, a metalling bar coater, a gravure roll coater, a reverse roll coater, a dip coater, or a die coater can be used.
[0060] In the above step (2), the drying method after coating is not particularly limited, and a conventional method can be used, for example, a method of drying using a known dryer such as an arch dryer, a straight bath dryer, a tower dryer, a drum dryer, or a floating dryer. The drying temperature varies depending on the heat resistance of the base film, but is usually from 50°C to 200°C, preferably from 70°C to 150°C, and more preferably from 100°C to 130°C, and the drying time is usually from 5 seconds to 10 minutes, preferably from 5 seconds to 3 minutes, and more preferably from 5 seconds to 1 minute.
[0061] The dried film may be aged in an oven or the like to further promote crystallization. For example, the dried film may be aged at 23°C, but in order to shorten the aging time and prevent damage to the film due to heating, the aging is preferably performed under temperature conditions of 30°C to 60°C, more preferably 35°C to 50°C, and even more preferably 35°C to 45°C. The aging time varies depending on the temperature conditions, but the aging is preferably performed for about 1 hour to 70 hours, more preferably 1.5 hours to 50 hours, even more preferably 3 hours to 50 hours, and even more preferably 5 hours to 50 hours. Such an aging treatment promotes crystallization of the polyvinylidene chloride resin, and the crystallinity of the polyvinylidene chloride resin constituting the polyvinylidene chloride resin layer 101 can be improved. As a result, the barrier film 100 according to this embodiment can be obtained.
[0062] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted. EXAMPLES
[0063] The present embodiment will be described in detail below with reference to examples and comparative examples, but the present embodiment is not limited to the descriptions of these examples.
[0064] The preparation of the liquids and the evaluations in the examples and comparative examples were carried out in the following manner.
[0065] (Measurement of peak ratio (A(1046) / A(1070)) The peak ratio (A(1046) / A(1070)) of the polyvinylidene chloride resin layer constituting the barrier film was measured by the following method. A measurement sample of 1 cm x 3 cm was cut out from the barrier films obtained in the Examples and Comparative Examples, and the infrared absorption spectrum of the surface (polyvinylidene chloride resin layer) was obtained by infrared total reflection measurement (ATR method) to determine the peak ratio (A(1046) / A(1070)). The infrared spectrum was measured (attenuated total reflection (ATR) method) using a JASCO FT-IR350 instrument, equipped with a KRS-5 (Thallium Bromide-Iodide) crystal, at an incidence angle of 45 degrees, at room temperature, and with a resolution of 4 cm. -1 The test was performed with 150 cumulative measurements.
[0066] (Oxygen permeability measurement) The oxygen permeability was measured in accordance with JIS K7126-2:2006. For the barrier films obtained in the examples and comparative examples, an adhesive (Takelac A-310 (product name) / Takenate A-3 (product name) = 12 / 1 (weight ratio) manufactured by Mitsui Chemicals) was applied at 3.0 g / m to a 50 μm-thick LLDPE film (manufactured by Mitsui Chemicals Tocello, product name: TUXFCS). 2 The barrier film was laminated so that the adhesive-coated surface of the LLDPE film was in contact with the surface of the barrier film opposite the base film layer. Next, the oxygen permeability of the resulting barrier film was measured at a temperature of 20° C. and a humidity of 90% RH using an oxygen permeability measuring device (OXTRAN2 / 21 manufactured by MOCON).
[0067] (Measurement of water vapor permeability) The coated film thus produced is placed in a container with an inner surface area of 0.01 m 2 A bag was made so that the bag would be filled with 10 g of calcium chloride, and the opening of the bag was heat-sealed. The resulting bag was then stored in an environment of 40° C. temperature and 90% RH for 72 hours. The weight of calcium chloride was measured before and after storage, and the water vapor permeability was calculated from the difference [unit: g / (m 2 ·d)]
[0068] (Determining the turbidity of the coating liquid) A piece of paper with black letters printed on a white background was placed vertically. A 5% solution was placed in a cylindrical transparent glass bottle with a diameter of 4 cm, and when the bottle was pressed against the letters and viewed from the front, if the letters were legible they were rated as A, if they were illegible they were rated as B, and if the existence of the letters could not even be recognized they were rated as C.
[0069] (Preparation of solution A) Asahi Kasei polyvinylidene chloride resin (Saran TM Resin R204) was dissolved in a mixed solvent of toluene:tetrahydrofuran = 2:1 heated to 50 ° C to prepare a 5% solution. It was then cooled to room temperature and left for 3 days to prepare liquid A. (Preparation of solution B) Asahi Kasei polyvinylidene chloride resin (Saran TM Resin R204) was dissolved in a mixed solvent of toluene:tetrahydrofuran = 1:2 heated to 50 °C to prepare a 5% solution. It was then cooled to room temperature and left for 3 days to prepare liquid B. Liquids A and B were left to stand at room temperature for three days before use. When liquids A and B were mixed, they were used immediately after being left to stand for three days.
[0070] [Example 1] A 12 μm biaxially oriented polyethylene terephthalate film (manufactured by Unitika Ltd., product name Emplet PET#12) was used as the base film. Liquid A was applied as a coating liquid to the corona-treated surface with a Mayer bar and dried in an oven at 100° C. for 30 seconds to obtain a coating amount of 1.1 g / m 2 A polyvinylidene chloride laminate film of (solid content) was obtained. After that, it was aged in an oven at 40°C for 3 days, and the IR peak ratio and water vapor transmission rate of the sample were measured. The turbidity level of the liquid at the time of coating was C.
[0071] [Example 2] A sample was prepared in the same manner as in the example, except that the coating liquid was a mixture of liquid A and liquid B (liquid A: liquid B = 75:25), and the IR peak ratio and water vapor transmission rate were measured. The turbidity level of the liquid during coating was C.
[0072] [Example 3] A sample was prepared in the same manner as in Example 1, except that the coating liquid was a mixture of liquid A and liquid B (liquid A:liquid B = 50:50), and the IR peak ratio and water vapor transmission rate were measured. The turbidity level of the liquid during coating was C.
[0073] [Example 4] A sample was prepared in the same manner as in Example 1, except that the coating liquid was a mixture of liquid A and liquid B (liquid A:liquid B=25:75), and the IR peak ratio and water vapor transmission rate were measured. The turbidity level of the liquid during coating was B.
[0074] [Comparative Example 1] A sample was prepared in the same manner as in Example 1, except that the coating liquid was 100% Liquid B, and the IR peak ratio and water vapor transmission rate were measured. The turbidity level of the coating liquid was A. The results are shown in Table 1. The relationship between the ratio of solution B shown in Table 1 and the water vapor transmission rate, and the relationship between the ratio of solution B shown in Table 1 and the change in the IR peak ratio are shown in Figures 4 and 5, respectively.
[0075] [Table 1]
[0076] The barrier films of Examples 1 to 4 have a water vapor permeability of 5.0 g / m 2 In contrast, the water vapor permeability was high in Comparative Example 1, and the barrier properties were clearly inferior. [Explanation of symbols]
[0077] 100 Barrier film 101 Polyvinylidene chloride resin layer 103 Base film layer 105 Inorganic layer
Claims
1. A barrier film comprising at least a polyvinylidene chloride resin layer containing a polyvinylidene chloride resin as a main component, In the infrared absorption spectrum of the polyvinylidene chloride resin layer, -1 1046 cm for the absorption peak height A (1070) at a wave number in the vicinity of -1 A barrier film having a peak ratio (A(1046) / A(1070)) of absorption peak height A(1046) at a wave number in the vicinity of 2.10 or more (however, this does not include a gas barrier laminate film having an excellent print finish, which is formed by laminating, via an adhesive layer, the printed surface of a base film printed on one side and the polyvinylidene chloride resin coated surface of a heat sealable film having a polyvinylidene chloride resin coating layer on one side.
2. The barrier film according to claim 1 , A barrier film having a base film layer on at least one side of the polyvinylidene chloride resin layer.
3. The barrier film according to claim 2, A barrier film having an inorganic layer between the polyvinylidene chloride resin layer and the base film layer.
4. The barrier film according to claim 3, The barrier film, wherein the inorganic layer contains one or more inorganic materials selected from the group consisting of silicon oxide, silicon oxynitride, silicon nitride, aluminum oxide, and aluminum.
5. The barrier film according to any one of claims 2 to 4, A barrier film having a polyester-based adhesive layer between the base film layer and the polyvinylidene chloride-based resin layer.
6. The barrier film according to any one of claims 1 to 5, The polyvinylidene chloride resin layer comprises one or more adhesive components selected from the group consisting of a silane coupling agent, a urethane resin, a urea resin, a melamine resin, an epoxy resin, and an alkyd resin.
7. A barrier packaging material comprising the barrier film according to any one of claims 1 to 6.
Citation Information
Patent Citations
JP1973018318B1
Gas barrier property laminated film
JP1985190352A
Gas barrier coating agent
JP1991054244A
Vacuum-deposited composite film and its production
JP1996039718A
Medical instrument packaging material
JP1998156996A